KOMPETENSI TUTOR DALAM MENGAJAR PADA PENDIDIKAN KESETARAAN DI SANGGAR KEGIATAN BELAJAR (SKB) KOTA PEKANBARU PROVINSI RIAU - Ayu Sri Devi; Wilson Wilson; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the competence of teachers in education in equality education in the Learning Activity Studio (SKB) of Pekanbaru City, Riau Province. The sample in this study was 30 people, namely the equality education tutor of the Pekanbaru City Learning Activity Center (SKB) with a saturated (total) sampling technique. The technique to collect data using a questionnaire. Data analysis techniques using the SPSS program and percentage calculation. The results of this study indicate that the competence of Teaching in Education for Equality in the Learning Activity Studio (SKB) of Pekanbaru City in Riau Province is reasonably good at planning and that implementing learning is reasonably good , starting with the preparatory activities, core activities and closing activities. to learn. Moreover, when performing the assessment of learning, it is still reasonably good.Key Words: Teacher Competence, Education, Equality Education, Studio Guidance Activities In Pekanbaru City